Durability of Composites in a Marine Environment 2 - Davies, Peter; Rajapakse, Yapa D.S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents selected papers from the 2nd Workshop on "Durability of Composites in a Marine Environment", which was held in Brest, France in August 2016. Providing an overview of the state of the art in predicting the long-term durability of composite marine structures, it addresses modelling water diffusion; damage induced by water accelerated testing, including durability in design; in-service experiences; ocean energy; and offshore applications. Ensuring long-term durability is not only necessary for safety reasons, but also determines the economic viability of future marine structures, and as such, the book is essential reading for all those involved with composites in the marine industry, from initial design and calculation through to manufacture and service exploitation. It also provides information unavailable elsewhere on the mechanisms involved in degradation and how to take account of them.   .
Introduction -- Non-Empirical Kinetic Modelling of Non-Fickian Water Absorption Induced by a Chemical Reaction in Epoxy-Amine Networks -- Influence of Glass Fibre Sizing and Storage Conditions on Composite Properties -- Water Uptake in Polymer Composites with Voids -- Durability of US Naval Composites and Sandwich Structures: Science Framework Considering Multi-Scale Response in Harsh Sea Environment -- Statistical Long Term Creep Failure Time of Unidirectional CFRP -- Multiphysics Modeling of the Hygro-Mechanical Behavior of Heterogeneous Materials -- Reliability of Composite Marine Structures -- Multi-Scale Modelling of Environmental Degradation - First Steps -- Present and Future Composites Requirements for the Offshore Oil and Gas Industry -- Composite Materials in Tidal Energy Blades -- Influence of Composite Fatigue Properties on Marine Tidal Turbine Blade Design -- Marine Ageing Behaviour of New Environmentally-Friendly Composites.
Keywords: Ceramic materials; Offshore structures; Polymers; Ceramics; Offshore Engineering; Polymers